SURFACE TOPOGRAPHICAL CHANGE DUE TO SLIDING CONTACT - . Jamari; E. Saputra; R. Ismail; M. Taviqirrahman; D.J. Schipper (Prosiding SNST Fakultas Teknik, 2010)
Many engineering applications often involve contacting surfaces. The contact can be either in the form of sliding, rolling or a combination of sliding and rolling. Sliding contact between mechanical components such as gears and cam and followers will result in wear. Wear is caused by mechanical or chemical interactions, and is a highly complex phenomenon. The mechanical engineers who faced the immediate problem of wear control in machinery had however to respond to the situation by formulating first order models based on purely mechanical concepts. This paper presents a model to predict the change of surface topography due to sliding contact or wear. The surface topography is represented by an asperity. The general Archard’s wear equation is employed in combination with finite element analysis for constructing the model. The development of contact pressure distribution and geometrical change are investigated as a function of sliding distance. Results show that for the same contact condition the wear depth of the asperity is affected dominantly by the sliding distance. Keywords: asperity, sliding contact, wear, elastic-plastic contact, finite element analysis.